Rancang Bangun Mesin Pemotong Karet Gelang - Sepriyanto; Sigit Kurniawan (Jurnal INOVATOR, 2021)
Rubber plant is one of the potential plants, the production of latex from the rubber plant is used as a raw material for making rubber bands, and the cutting process is required by a rubber band cutting machine. The purpose of the performance analysis of this rubber band cutter is to find out the cut / minute results of this machine and the machine uses a 1.5 HP electric motor with a reducer ratio of 10: 1 and get a 110 Cut / minute result and from the results of data retrieval using a thick cutting knife 5 mm on average this machine can print granules with a thickness of 2 mm. As for this machine, it will be sold at a more economical price and uses a level of electricity consumption that is not wasteful compared to machines that are already on the market.